Pilot Study for Azoxymethane-induced Colon Cancer in Male Wistar Rats - Taufik, Riska; Pandianta, Abidin; Kusuma, Rinaldy; Winoto, Imelda L.; Suriapranata, Ivet; Mathew, George (Medicinus, 2019)
Introduction : The use of animal models could significantly further the elucidation of Colorectal Cancer (CRC) molecular pathogenesis and help in the discovery of preventive and therapeutic agents for the disease. Dimethylhydrazine (DMH) is a widely used chemical agent for Carcinogen induced CRC model. As agent, DMH is however becoming less readily available; hence in this Pilot Study we use Azoxymethane (AOM), a DMH metabolite as an alternative agent to induce CRC in male Wistar rats. Methods: Forty two male Wistar rats at six weeks of age were randomly assigned into negative control groups and groups receiving two AOM injections subcutaneously (SC) within one week interval at 15 mg/kg body weight (BW) and 20 mg/kg BW respectively. Rats were sacrificed 8, 16 and 24 weeks post- AOM administration. Aberrant crypt foci (ACF) were analyzed. Tumor foci were characterized by gross examination and histopathological characteristics. Results: All rats in the AOM groups developed tumors in the colonic mucosa. Formation of ACF was detected starting from 8 weeks post-AOM injection. The highest number of ACF with multiple crypts was observed at 16 weeks post-AOM administration. The total number of ACF did not vary between the two AOM doses. Mild, moderate and severe dysplastic cells were observed in colonic mucosa starting 8 weeks post-AOM injection. There was no statistically significant difference between number of severe dysplastic cells between the two AOM doses. Conclusion: Administration of AOM 15 mg/kg BW SC is able to induce CRC in male Wistar rats. Higher dose is not necessary since it does not result in higher tumor incidence. This cancer model may be utilized to study chemopreventive effect of various agents in the future.